PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA BERBASIS GAMIFIKASI PADA MATA PELAJARAN EKONOMI - Oktafia, Melinda Ayu; Fitrayati, Dhiah (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This study aims to develop teaching materials for snakes and ladders games, determine the feasibility of snakes and ladders learning media and the effectiveness of gamification-based snakes and ladders learning media. The limited experiment was limited to class X SMA Hang Tuah 2 Sidoarjo by dividing into control and experimental classes. This research uses the ADDIE development method with an R&D approach model conducted on grade X students of Hang Tuah 2 Sidoarjo High School. The data acquisition technique is done through a validation questionnaire to determine the feasibility of teaching materials and to determine the effectiveness of snakes and ladders media by using student learning outcomes. The results of data analysis refer to the results of the pre-test and post-test which are used to determine the increase in student learning outcomes, namely the N-Gain Test. The results showed that snakes and ladders learning media were able to improve student learning outcomes with the average value of N-Gain in the experimental group classified as high criteria. There is a significant difference in the improvement of student learning outcomes between the control group and the experimental group. Therefore, snakes and ladders learning media in economic subjects are suitable for use as one of the learning media for students in class X SMA / MA